2015
DOI: 10.1073/pnas.1416851112
|View full text |Cite
|
Sign up to set email alerts
|

Role of the motor system in language knowledge

Abstract: All spoken languages express words by sound patterns, and certain patterns (e.g., blog) are systematically preferred to others (e.g., lbog). What principles account for such preferences: does the language system encode abstract rules banning syllables like lbog, or does their dislike reflect the increased motor demands associated with speech production? More generally, we ask whether linguistic knowledge is fully embodied or whether some linguistic principles could potentially be abstract. To address this ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 45 publications
1
16
2
Order By: Relevance
“…We attribute this imbalance to the fact that all subjects were right-handed (Tettamanti et al, 2005 ). Activity in the premotor cortices as preparation of words referring to motor acts is well documented in numerous neuroimaging studies in which words were presented either visually or acoustically or both (Hauk et al, 2004 ; Pulvermuller, 2005 ; D'Ausilio et al, 2009 ; Cappa and Pulvermüller, 2012 ; Berent et al, 2015 ). In our study, the pattern of response to audio-visual word presentation also involved the left primary motor cortex, where BA 4 and BA 7 play a role in motor sequence coordination, visuo-motor coordination, planning of complex movements, and proprioception (Baker et al, 2012 ).…”
Section: Methodsmentioning
confidence: 98%
“…We attribute this imbalance to the fact that all subjects were right-handed (Tettamanti et al, 2005 ). Activity in the premotor cortices as preparation of words referring to motor acts is well documented in numerous neuroimaging studies in which words were presented either visually or acoustically or both (Hauk et al, 2004 ; Pulvermuller, 2005 ; D'Ausilio et al, 2009 ; Cappa and Pulvermüller, 2012 ; Berent et al, 2015 ). In our study, the pattern of response to audio-visual word presentation also involved the left primary motor cortex, where BA 4 and BA 7 play a role in motor sequence coordination, visuo-motor coordination, planning of complex movements, and proprioception (Baker et al, 2012 ).…”
Section: Methodsmentioning
confidence: 98%
“…4 pulses were sent for every word, with 50-ms gaps between consecutive pulses), based on previous studies which on the one hand demonstrated local interference effects following this protocol and on the other hand excluded any inter-hemispheric effect (Hamada and Ugawa 2010;Tsutsumi et al 2014;Gerloff et al 1997;Rossi et al 2002Rossi et al , 2006Rossi et al , 2011Berent et al 2015).…”
Section: Tms Protocolmentioning
confidence: 99%
“…Other results speak against an articulatory motor explanation-the possibility that people misidentify ill-formed syllables because they have difficulties in tacitly generating their motor plan. Contrary to the motor account, ill-formed syllables disengage the articulatory system ; and their misidentification persists even when articulatory motor system is suppressed by Transcrnial Magnetic Stimulation (Berent et al 2015). Moreover, the results obtain with speakers of various languages (English: Berent et al 2007;French: Maïonchi-Pino et al 2012;Korean: Berent et al 2008;Spanish: Berent et al 2012a, b) and despite minimal linguistic and articulatory experience-in the brains of neonates (Gómez et al 2014).…”
Section: Introductionmentioning
confidence: 96%